Histone demethylase AMX-1 is necessary for proper sensitivity to interstrand crosslink DNA damage. - Xiaojuan Zhang (Public Library of Science (PLoS), 2021)
Histone methylation is dynamically regulated to shape the epigenome and adjust central nuclear processes including transcription, cell cycle control and DNA repair. Lysine-specific histone demethylase 2 (LSD2) has been implicated in multiple types of human cancers. However, its functions remain poorly understood. This study investigated the histone demethylase LSD2 homolog AMX-1 in C. elegans and uncovered a potential link between H3K4me2 modulation and DNA interstrand crosslink (ICL) repair. AMX-1 is a histone demethylase and mainly localizes to embryonic cells, the mitotic gut and sheath cells. Lack of AMX-1 expression resulted in embryonic lethality, a decreased brood size and disorganized premeiotic tip germline nuclei. Expression of AMX-1 and of the histone H3K4 demethylase SPR-5 is reciprocally up-regulated upon lack of each other and the mutants show increased H3K4me2 levels in the germline, indicating that AMX-1 and SPR-5 regulate H3K4me2 demethylation. Loss of AMX-1 function activates the CHK-1 kinase acting downstream of ATR and leads to the accumulation of RAD-51 foci and increased DNA damage-dependent apoptosis in the germline. AMX-1 is required for the proper expression of mismatch repair component MutL/MLH-1 and sensitivity against ICLs. Interestingly, formation of ICLs lead to ubiquitination-dependent subcellular relocalization of AMX-1. Taken together, our data suggest that AMX-1 functions in ICL repair in the germline.